2019
DOI: 10.1021/acsami.9b09941
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Effect on CO2 Electroreduction by Hydroxyl-Terminated Two-Dimensional MXenes

Abstract: Electrocatalysis represents a promising method to generate renewable fuels and chemical feedstock from the carbon dioxide reduction reaction (CO 2 RR). However, traditional electrocatalysts based on transition metals are not efficient enough because of the high overpotential and slow turnover. MXenes, a family of two-dimensional metal carbides and nitrides, have been predicted to be effective in catalyzing CO 2 RR, but a systematic investigation into their catalytic performance is lacking, especially on hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 47 publications
0
73
0
Order By: Relevance
“…Therefore, with variations in either M, X or T x components, different interactions with CO 2 RR intermediates can be expected. Calculations on (perfect) MXenes have shown atypical intermediates for CO 2 RR to CH 4 , involving both −H‐ and −C‐coordinated intermediates [6b–d] . However, we note that systematic studies on more realistic, defective MXenes structures for CO 2 RR are absent.…”
Section: Introductionmentioning
confidence: 77%
“…Therefore, with variations in either M, X or T x components, different interactions with CO 2 RR intermediates can be expected. Calculations on (perfect) MXenes have shown atypical intermediates for CO 2 RR to CH 4 , involving both −H‐ and −C‐coordinated intermediates [6b–d] . However, we note that systematic studies on more realistic, defective MXenes structures for CO 2 RR are absent.…”
Section: Introductionmentioning
confidence: 77%
“…The O termination groups on MXenes help to stabilize reaction intermediates through H coordination, resulting in marked departure from *CO binding strength as the main CO 2 RR activity descriptor observed on transition metal catalysts. [119] Chen et al [120] utilized the first-principles approach to systematically explore CO 2 RR properties on 17 different MXenes with OH termination groups from both aspects of thermodynamics and kinetics, and found that Sc 2 C(OH) 2 and Y 2 C(OH) 2 the most promising catalysts with limiting potential of −0.53 and −0.61 V, respectively, which was obviously less negative than Cu metal. At the same time, the competing HER was disfavored due to strong H binding.…”
Section: Carbon Dioxide Reduction Reactionmentioning
confidence: 99%
“…Reproduced with permission. [ 131 ] Copyright 2019, American Chemical Society. c) DFT study of electrochemical nitrogen reduction based on functionalized MXenes, i) schematic illustration of the nitrogen reduction process on the surface of MXenes; ii) calculated pourbaix diagrams for Mo 2 C with different functional groups, the relative stability at an applied voltage is referenced to the free energy of the bare Mo 2 C MXene; iii) calculated free energy diagrams for NRR mechanism on Mo 2 C MXene with different terminations.…”
Section: The Application Of Mxenesmentioning
confidence: 99%